Integrating rapport-building into language instruction: A study of Korean foreign language classes. Issue 2 (3rd May 2016) - Park, Mi Yung
Abstract : Using a conversation-analytic approach along with the notions of frame and footing (Goffman1981 ), this study examines what strategies teachers use to build rapport with their students in Korean as a foreign language classrooms. It also discusses what kinds of interactional resources they employ in tandem with these strategies. Analysis of teacher–student interactions in different sequential contexts demonstrates that teachers occasionally integrate rapport-building into an ongoing interaction by negotiating different footings and frames, such as a formal, institutional frame and an informal, conversational frame. This study highlights the teachers' use of four strategies: engaging students in informal conversations, integrating humour into classroom interactions, softening corrections with compliments and demonstrating empathy toward students. By paying attention to the teachers' shifts in footings and frames, the study expands our understanding of the intricate verbal and non-verbal manoeuvres involved in the task of building rapport in a foreign language classroom. The findings, which show that the language classroom is a social space in which teachers and students not only co-construct knowledge but also build relationships, have pedagogical implications. In addition, this study contributes to raising awareness of the teacher's critical role in creating a positive learning environment.